2015
DOI: 10.1002/dvdy.24299
|View full text |Cite
|
Sign up to set email alerts
|

YPEL1 overexpression in early avian craniofacial mesenchyme causes mandibular dysmorphogenesis by up‐regulating apoptosis

Abstract: Background: The YPEL (Yippee-like) gene family comprises five highly conserved members (YPEL1-5), but their biological function remains largely unknown. Early studies of YPEL1 function suggested that it plays a role in the development of structures derived from the pharyngeal arches. Human YPEL1 localises to distal chromosome 22q11.2 and copy number changes at this locus lead to diverse phenotypes that include facial dysmorphism, facial asymmetry, and palatal anomalies comprising the distal 22q11.2 deletion/du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In fact, few study reported the pathways YPEL1 may participate because it is a newly identified protein. It has been reported that YPEL1-related abnormal mandibular morphogenesis was associated with increased apoptosis and involvement of the BMP/MSX pathway (Tan et al 2015), which can serve as an inspiration for validating its mechanisms in malignancies in the near future. Nevertheless, our paper represents the first evidence on confirming YPEL1's role in glioma both in vitro and in vivo, highlighting its potential as a novel therapeutic target.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, few study reported the pathways YPEL1 may participate because it is a newly identified protein. It has been reported that YPEL1-related abnormal mandibular morphogenesis was associated with increased apoptosis and involvement of the BMP/MSX pathway (Tan et al 2015), which can serve as an inspiration for validating its mechanisms in malignancies in the near future. Nevertheless, our paper represents the first evidence on confirming YPEL1's role in glioma both in vitro and in vivo, highlighting its potential as a novel therapeutic target.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, YPEL1 may participate in modulating cellular morphology and behavior that is important for development of the craniofacial complex (Farlie et al 2001). Indeed, a recent study reported that YPEL1 overexpression in early avian craniofacial mesenchyme causes mandibular dysmorphogenesis by up-regulating apoptosis (Tan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After the first selection, there were five human studies that met the above-mentioned requirements: two cross-sectional studies [13,18] and three case-control studies [11,19,20]. Four animal studies were also selected: one case-control study [16] and three experimental studies [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Yang Tan et al [22] investigated the impact of YPEL1 overexpression on the mandible. Their publication is an experimental study that was conducted on chicken embryos.…”
Section: Ypel1mentioning
confidence: 99%
“…Subtype 10 specifically expressed PO4F3 (POU class 4 homeobox 3), which has been reported to be expressed in the touch plate (hair-cell-bearing mechanosensory organ) of rhopalia in moon jellyfish Aurelia sp.1 35 (Figure 5b). This subtype also specifically expresses the genes YPEL1 (yippee-like protein 1), ANPRB (natriuretic peptide receptor 2), SRPK1 (SRSF protein kinase 1), NCOR1 (nuclear receptor corepressor 1), LRC71 (leucine-rich repeat-containing protein 71) and SMAG2 (protein Smaug homolog 2), which is correlated with neuronal development of the central nervous system [36][37][38][39][40] (Figure 5b). Notably, several ion channel-related genes preprint (which was not certified by peer review) is the author/funder.…”
Section: Identification Of Newly Emerged Neural Cell Types During The...mentioning
confidence: 99%